Safety, Pharmacokinetics and Pharmacodynamics of Spectrum Yellow Oil in Healthy Participants. Issue 4 (12th March 2021) - Peters, Erica N; Mosesova, Irina; MacNair, Laura; Vandrey, Ryan; Land, M Hunter; Ware, Mark A; Turcotte, Cynthia; Bonn-Miller, Marcel O
Abstract: Due to a lack of published pharmacokinetic (PK) and/or pharmacodynamic (PD) data, decision-making surrounding appropriate dosing of cannabis used for medical purposes is limited. This multiple-dose study evaluated the safety, tolerability, PK and PD of Spectrum Yellow oil [20 mg/mL cannabidiol (CBD)/<1 mg/mL ∆ 9 -tetrahydrocannabinol (THC)]. Participants ( n = 43) were randomized to one of five groups: 120 mg CBD and 5.4 mg THC daily, 240 mg CBD and 10.8 mg THC daily, 360 mg CBD and 16.2 mg THC daily, 480 mg CBD and 21.6 mg THC daily or placebo. Study medication was administered every 12 h for 7 consecutive days. Treatment-emergent adverse events (TEAEs); plasma and urine concentrations of THC, CBD and metabolites; and self-reported subjective effects were collected. Nearly all TEAEs (44/45) were of mild or moderate severity; none was serious. The highest incidence of TEAEs (67%) was in the two higher-dose treatment groups. The highest number of TEAEs (17/45) occurred on the first treatment day. Steady-state plasma CBD concentrations were reached by Day 7. On Day 7, CBD exposure showed dose proportionality (AUC0– t slope = 1.03 [0.70, 1.36], C max slope = 0.92 [0.53, 1.31]). Most plasma THC concentrations were below the limit of quantification. Across Days 1 and 7, there were no consistent differences in subjective effects between placebo and active study medication. A prudent approach to improve tolerability with Spectrum Yellow oil might involve initial doses no higher than 240 mg total CBD and 10.8 mg total THC daily in divided doses, with titration upward over time as needed based on tolerability.